Thinking about an anthropological gender research in Brazil - Maia, J. V. (16th EASA Biennial Conference - New anthropological horizons beyond Europe, 2020)
An attempt to understand how the gender relations of the present take place as part and consequence of multi-layered historical and political processes suggests also thinking about these other layers and the way in which their meanings pass through the lives of women and men. In Brazil, it is possible to situate gender relations as part and consequence of colonial processes - Carneiro (2003) states that the colonial rape and its consequent miscegenation "is at the origin of all the constructions of our [brazilian] national identity". In this sense, it can be valuable looking for reflections since Mignolo's (2000) thesis about a modern-colonial order in Latin America - and, consequently, in Brazil. The author's idea thinks about reality today as part of many simultaneous dynamics that still happening under colonial rules and its reproduction. The hypotesis here is try to find clues to understand if and how gender relations are simultaneously as structured and structured by this modernity/coloniality. The concept of intersectionality (Crenshaw, 2002; Collins, 1990) is also valuable for this reflection by overlaping patriarchy with other layers of domination, such as race and ethnicity, social class, nationality and age. Finally, a question that poses is how to transfer these theoretical reflections in epistemic and methodological processes that challenge modernity-coloniality while being integrated with the academic practices that have historically been sustained by this modern reason.